Orienting spins in dually doped monolayer MoS2: from one-sided to double-sided doping. Issue 39 (2nd May 2017) - Vähäkangas, J.; Lantto, P.; Vaara, J.; Huttula, M.; Cao, W.
Abstract : Single- and double-sided doped monolayer MoS2 show electron spin alignments with their origins beyond explanations of the existing models. Abstract : Electron spins of the doped monolayer MoS2 were aligned by placing two magnetic impurities at sulfur vacancies, both on the same side and different sides of the slab. Origins of the calculated magnetisms are beyond most conventional physical models, yet interactions of single-molecule magnets are tentatively proposed.